STRATEGI PENGEMBANGAN WISATA ALAM TAMAN GUA SIGROWONG DI DESA GESING, KECAMATAN KANDANGAN, KABUPATEN TEMANGGUNG - Sukma Indah Fitri; R Slamet Santoso; Retna Hanani (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2023)
Sigrowong Cave Park is a tourist destination located in Gesing Village, Kandangan District, Temanggung Regency. However, the park faces several problems such as inadequate quantity and quality of human resources, inadequate facilities and infrastructure that are not maintained, minimal management budget, lack of investors, and no cooperation with the local government. This study aims to analyze the internal and external environment of tourism development and determine the tourism development strategy of Sigrowong Cave Park. The research method used is descriptive and explorative qualitative, using observation, interview, documentation, and literature data collection techniques with primary and secondary data sources. The study uses the strategic planning theory from John M. Bryson and the SWOT analysis approach. The results of the study show that the EFAS and IFAS calculations are in quadrant 1, where Sigrowong Cave Park can take advantage of its strengths to seize as many available opportunities as possible and formulate relevant strategic issues. To develop Sigrowong Cave Park, several strategies can be employed, including maximizing tourism potential by combining the themes of natural collaboration and community culture, strengthening tourism development efforts, maximizing the potential of tourism objects, community participation in tourism innovation, and holding and displaying cultural events once a month and for annual events. Additionally, optimizing collaboration with the surrounding community by holding regular events such as the pine market innovation and maximizing cooperation with the community in tourism management.In conclusion, the study recommends four development strategic issues that can be used and formulated to make recommendations for programs and activities in developing the Sigrowong Cave Park tourist attraction.